Insights into the mechanism of high lipid–detergent crystallization of membrane proteins. Issue 6 (25th November 2021) - Trampari, Sofia; Neumann, Caroline; Hjorth-Jensen, Samuel J.; Shahsavar, Azadeh; Quistgaard, Esben M.; Nissen, Poul
Abstract : High lipid–detergent crystallization of two model membrane proteins, MhsT and SERCA1a, where the effects of varying lipid/detergent ratio were tested, and the resulting lipid phases and crystals were studied using electron microscopy, providing insights into the crystallization mechanism. Abstract : Obtaining well diffracting crystals of membrane proteins is often challenging, but chances can be improved by crystallizing them in lipidic conditions that mimic their natural membrane environments. One approach is the high lipid–detergent (HiLiDe) method, which works by mixing the target protein with high concentrations of lipid and detergent prior to crystallization. Although this approach is convenient and flexible, understanding the effects of systematically varying lipid/detergent ratios and a characterization of the lipid phases that form during crystallization would be useful. Here, a HiLiDe phase diagram is reported for the model membrane protein MhsT, which tracks the precipitation and crystallization zones as a function of lipid and detergent concentrations, and is augmented with data on crystal sizes and diffraction properties. Additionally, the crystallization of SERCA1a solubilized directly with native lipids is characterized as a function of detergent concentration. Finally, HiLiDe crystallization drops are analysed with transmission electron microscopy, which among other features reveals liposomes, stacked lamellae that may represent crystal precursors, and mature crystals with clearly discernible packing arrangements. The results emphasize the significance of optimizing lipid/detergent ratios over broad ranges and provide insights into the mechanism of HiLiDe crystallization.